Sprog og kognition i evolutionshistorien - Ulbæk, Ib (Psyke & Logos, 2022)
This paper demonstrates the usefulness of evolutionary analysis in understanding the relation between language and cognition and their origins. It is claimed that language and the other cognitive phenomena consists in individual competences on which the behavior is founded. Natural selection is considered the prime cause in bringing these competences about. Cognitive competences have a biological function in adapting the organism to its physical and social environment, and is existing in other species than the Homo sapiens. Why is language existing only in the human species considering the great advantage it seems to confer on its owner? It is shown that there is a major difference in language and the other cognitive competences. Language depends on special social interaction because of its altruistic nature. Other cognitive competences are selfish, serving the individual. Language could only develop in a group where cooperation was widespead. Cooperation is not a general phenomena in nature but existing in the early hominds. The prerequisitions of language is an advanced cognitive protohuman on whose propositional thinking the language could be shaped. From the possibility of making reliable communication the language module could evolve. The language origin in this theory is not connected to animal cornmunication systems but to the prior development of an intelligent being: a cognitive animal.